Pengaruh Pupuk Organik Cair (POC) dan Zat Perangsang Akar Pada Pertumbuhan Bibit Stek Tanaman Mangga Apel (Mangifera indica L.) - Mahmul Salim Siregar; Rizky Amnah; Meiliana Friska (Yayasan Perguruan Kampus, 2024)
This research aims to determine the effect of administering several types of POC doses and the effect of various types of ZPA soaking on mango stem cuttings. This research was conducted from June to July 2023. This research used the RAK (Randomized Group Factorial Design) method with 2 factors, namely 1. Dose P0 = No treatment, P1 = 3ml POC dose, P2 = 5ml POC dose. 2. Length of soaking Z0 = No Treatment, Z1 = Length of Soaking 6 Hours, Z2 = Length of Soaking 12 hours, and Z3 = Length of Soaking 18 hours Parameters observed were Percentage of life, Number of shoots, height of shoots (cm), number of leaves, number root eye. The total number of living cuttings was 75% of the 36 cuttings and the dead were 9 cuttings.